2004
DOI: 10.1007/s15010-004-3063-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Hepatitis C Virus Coinfection: Epidemiology, Natural History, Therapeutic Options and Clinical Management

Abstract: Due to shared risk factors for transmission, coinfection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) is a very common event. The prevalence of HCV infection among HIV-positive patients averages about 35% in the United States and Europe, but in clinical populations where there is a great prevalence of intravenous drug use as a risk factor for acquiring HIV, this value may be as high as 80-90%. Several studies have confirmed that HIV coinfection accelerates the natural course of chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 113 publications
(196 reference statements)
3
73
2
2
Order By: Relevance
“…Newly HIV infected patients who received their HIV status after the data collection started and HIV patients less than 18 years old were excluded due to difficulty of obtaining consent.…”
Section: Study Subjects and Sampling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly HIV infected patients who received their HIV status after the data collection started and HIV patients less than 18 years old were excluded due to difficulty of obtaining consent.…”
Section: Study Subjects and Sampling Proceduresmentioning
confidence: 99%
“…Approximately four to five million HIV patients are coinfected with HCV globally [3] . In these patients, HIV virus weakens the immune response to HCV resulting in a lower probability of spontaneous viral clearance of HCV infection, higher levels of HCV RNA in the blood, more rapid progression to HCV-related end stage liver disease and increased risk of antiretroviral associated liver toxicity [16][17][18] . The problems listed above highlight the importance of preventing further spread of HBV and HCV infections in HIV-infected patients as well as diagnosing existing infections.…”
Section: Introductionmentioning
confidence: 99%
“…Co-infection with HIV and hepatotropic viruses is a common growing public health problem [78]. Co-infection alters the natural history of each of these viruses in a peculiar way.…”
Section: Importance Of Co-infectionmentioning
confidence: 99%
“…There is controversy in this management up till date, because of the complex pathogenesis of these infections, potential drug interactions, the poor literature and information available about safety and efficacy of an interferon and ribavirin combination in this group of patients [78]. Studies have shown that virological response rates in co-infected persons treated with standard interferon plus ribavirin range from 18-40% and several studies with pegylated interferon plus ribavirin are inconclusive and its outcome poorly understood [76].…”
Section: Importance Of Co-infectionmentioning
confidence: 99%
“…These statements (see Paragraph 2 in Scetion 6) neglect that "victims" of HIV infection covered by the "… respect HR" principle, in turn become offenders when they themselves transmit HIV to a partner(s), thereby violating HR whether aware or unaware of their HIV status. This is further reflected, for example, in high risk behavior resulting in the spread of not only HIV but HBV, HCV, and other STIs or combinations thereof (Verucchi et al, 2004;Serpaggi et al, 2006;Urbanus et al, 2009). HCV has gained access to communities in Europe via social networks (Vachta et al, 2009).…”
Section: Legal Frameworkmentioning
confidence: 99%